Mulher presente: gênero na Política de Assistência Social - Santos, Eloísa Gabriel dos (2019)
This thesis analyzes the historical process developed since the beginning of the 20th century, knowing the scope of patriarchy in daily life and in the legislations that influenced the life of women and their renunciation in the Pre-Constitution period of 1988 and Post-Constitution of 1988. The advances achieved in a Constitution with strong social mobilization, where women played an important role, with the Charter of Brazilian Women and their participation through social organizations in the Popular Amendments. The construction of public policies that represented the process of citizenship attributed to the Constitution, such as the Organic Law of Social Assistance, recognition in the Magna Law of men and women as citizens of rights, but with little singularity for the right of women in social policies. The hypothesis that guided the study is the question: the National Social Assistance Policy in Brazil contributes to the visibility or invisibility of women as subjects of rights. Norms, Laws, Plans, Reports constitute the basis for understanding the presence of women within the Social Welfare Police, how the female gender is seen and how it feels assisted by this public policy. It can be concluded in the declarations of the workers, beneficiaries and documents systematized during the research that the space won by women in Social Assistance needs a way to be traveled so that their presence and participation in articulation with flags of struggle and fight against patriarchy to be effective